Manajemen Kurikulum Merdeka dalam Meningkatkan Mutu Pendidikan di SMP Negeri 2 Ploso Jombang - Ni'mah, Devi Khoirun; Sirojudin, Didin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The curriculum for Merdeka Learning has advanced to the point where it may be classified as under development. Right now, the government is emphasizing how important it is to use it in all educational settings. The Republic of Indonesia's Minister of Education and Culture, Nadiem Makarim, was there, and his presence encouraged the idea for curriculum adjustments, namely the autonomous learning curriculum. According to the curriculum concept known as